Coupling effect of phase change heat transfer on free surface in pure steam environment and thermocapillary convection in annular pool. (October 2019) - Zhang, Li; Li, You-Rong
Highlights: Effect of phase change heat transfer on thermocapillary flow is simulated. Radial temperature gradient near the cylinders increases due to phase change. The axial velocity caused by phase change is much less than the radial velocity. With the increase of Ma, flow cells near outer cylinders expand to inner cylinder. Ambient steam temperature and pressure have significant influence on the flow. Abstract: In order to reveal the coupling effect between surface phase change heat transfer in pure steam environment and thermocapillary convection in annular pool, we performed a series of three-dimensional numerical simulations by using the finite volume method based on the statistical evaporation rate theory. The inner and the outer radii of the annular pool are respectively 20 mm and 40 mm, the depth ranges from 1 mm to 20 mm. The selected working fluid is water with Prandtl number of 6.13. Results show that the radial temperature gradient on the free surface near the cylinders increases due to the latent heat absorbed and/or released as a result of phase change heat transfer, which leads to the increase of the thermocapillary force near the cylinders and the enhancement of the flow. Therefore, the isotherms converge to the cylinders. The axial velocity on the free surface caused by surface phase change is much less than the inward radial velocity. Flow pattern depends slightly on Marangoni number. But with the increase of Marangoni number, the flow is enhanced and the flow cells near the cylinders gradually expand to the middle of the annular pool. With the increase of the aspect ratio, thermocapillary convection is enhanced and the evaporation strengthens. With the increase of ambient steam temperature and pressure, the condensation mass flux near the inner cylinder increases, the radial temperature gradient rises, and thermocapillary convection strengthens. However, near the outer cylinder, it is the opposite.